2020
DOI: 10.2166/wst.2020.104
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and cost benefits of co-digesting food waste at wastewater treatment facilities

Abstract: The wastewater industry is undergoing a paradigm shift from focusing solely on treatment to incorporating concepts aimed at mitigating environmental impacts such as energy and nutrient recovery and water reuse. This study uses life cycle assessment and life cycle cost analysis to investigate the effect of expanding anaerobic digestion (AD) capacity and adding combined heat and power on environmental and cost indicators at a mid-sized wastewater treatment facility (WWTF) in Massachusetts, USA. Since 2014, Massa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…More critically, adding CHP shows promising results in all ELCA categories (Figure 2; Table 4). Although Idaho Power maintains a significant portion of its power production in the form of the clean hydropower, coal and natural gas combined account for roughly 30%, both of which are associated with higher amounts of carbon dioxide, nitrogen oxides, and sulfur dioxide emissions; with CHP reducing external power demands by ~60%, Global Warming Potential was reduced by 2.55 × 10 −7 kg CO 2 equivalent (Table 4a); results are consistent with those observed by Morelli et al (2020).…”
Section: Resultssupporting
confidence: 89%
“…More critically, adding CHP shows promising results in all ELCA categories (Figure 2; Table 4). Although Idaho Power maintains a significant portion of its power production in the form of the clean hydropower, coal and natural gas combined account for roughly 30%, both of which are associated with higher amounts of carbon dioxide, nitrogen oxides, and sulfur dioxide emissions; with CHP reducing external power demands by ~60%, Global Warming Potential was reduced by 2.55 × 10 −7 kg CO 2 equivalent (Table 4a); results are consistent with those observed by Morelli et al (2020).…”
Section: Resultssupporting
confidence: 89%
“…Further quantification of “public goods” benefits further increase this viability. After energy savings, ability to use digestate in land application is found to be a major factor in economic and environmental sustainability in many studies [ 78 , 79 ]. This may be of more limited use in the urban area described in this paper, as transport costs to land application sites will naturally be higher than in situations where farms and digesters are co-located.…”
Section: Resultsmentioning
confidence: 99%
“…Ammonia stripping is established at full scale with systems in the United States and Europe. At high airflow rates through a packed bed tower, ammonium in centrate can be converted into gaseous ammonia at ambient temperatures and a pH of 11 which is then followed by acid absorption to produce a liquid fertilizer solution (e.g., (NH 4 ) 2 SO 4 ), which is marketable as a standard agricultural fertilizer product. 32,37 Operation requires inputs of a base (e.g., NaOH), an acid (e.g., H 2 SO 4 ), and energy.…”
Section: Current Treatment Of Centrate and Biosolidsmentioning
confidence: 99%
“…In past studies, codigestion was shown to have reduced global warming potential (GWP) and eutrophication potential when compared to single-substrate digestion, 8 composting, 9 and landfilling. 10 While the addition of HSOW increases energy recovery, 11 it also increases nutrient concentrations in the digestate. Additional nutrients in the digestate may provide benefits if the digestate is land-applied; however, issues may arise if these nutrients enter surface water that is at risk of eutrophication and/or subject to stringent nutrient regulations.…”
Section: Introductionmentioning
confidence: 99%